Design and Performance Analysis of a Wine-bridge RC Harmonic Oscillation Generator with an Operational Amplifier - Boyan Karapenev (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2020)
This paper presents the special features of harmonic generators and their widespread use and in particular the design, simulation and experimental studies of a Wine-bridge RC generator with an operational amplifier. The results obtained are analyzed and compared. It can be deduced that the parameters of the output signal can be accurately realized - the necessary frequency and the amplitude by setting the parameters of the constituent components.